Primary Splenic Lymphoma (PSL): A Rare Presentation of Lymphoma (Anwer Khan Modern Medical College Journal, 2018)
Primary Splenic Lymphoma (PSL) is a rare neoplasm of the spleen. PSL is generally presented as B cell non-Hodgkin lymphoma. Primary involvement of the spleen by lymphoma is much less common than secondary involvement. It usually presents with nonspecific symptoms like left upper abdominal pain or discomfort due to splenomegaly, pyrexia, weight loss, night sweats and weakness. In this article, we are reporting a case of PSL in a 23 years old boy who presented with splenomegaly and non-specifc symptoms.Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 152-153